Penerapan Model Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI) untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa pada Mata Pelajaran Ekonomi di SMA Negeri 2 Denpasar - Windhi Indriyani; I Nyoman Sujana (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
The study aimed to find out (1) the improvement of student’s learning activity in economic subjects by implementing team assisted individualization model. (2) the improvement of student’s learning outcomes by implementing team assisted individualization model. This research was CAR that was done in 2 cycles. The subject was 45 tenth graders in SMA Negeri 2 Denpasar. The objects of the study were students’ learning activities and learning outcomes. The study was quantitative research where the data source used primary data. The data was collected through observation and test. The results showed that, (1) TAI model increase student’s learning activities, the average in the first cycle of 6.75 with active category, then in the second cycle it increased to 8,85 in the active category. (2) The implementation of the TAI improves student’s learning outcomes, with the average of 67.11 in the sufficient category, then in the second cycle it increased to 80,11 with a good category.